The impact of the development and maintenance of human resources in reducing the phenomenon of alienation Career Exploratory study of the views of a sample of the company\'s managers for mining and waterproofing - Shafaa Mohammad Ali Al-Azawi; Ather Abdullah Al-Sodani (Iraqi Journal for Administrative Sciences, 2025)
Aims on current research to recognize the reality of the policy of developing & Maintenance Human resources amount effect the phenomenon of the individual feeling of the employee in the expatriation in his work environment a an important and valuable source in all sectors in general and in the industrial sector specialty . The sample of the research was formed from (50) per capita than those in level organizatational first, second and third in the General company for mining industries and aquatic Insullation in Baghdad and a questionnaire was used as a tool for collecting the data and the researches depended on the(spss)program for processing the data. The most important conclusion is the success of the(HRM) in the mentioned company in its developing and Maintaining policies of the Human resources which participated in rasing morales of the employees and enhancing their belonging and making them more enthusiastic and less feeling of alienation.The research end with many recommendution one of wich was encouraging the Iraqi idustrial organizations which are seeking creativity and innovation to increase the freedom of the employees in expressing their openions and enlarge their participation to creat a situation of neation and embalance among the parts of the organization and transplant of trust and confidence among the managers and the employees increase loyalty and belongingness for them.